Compression and thermal conductivity characteristics of magnetorheological fluid-spacer fabric smart structures - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2012)
There have been many reported applications of magnetorheological fluids but very few in combinations with the textile structures. Increasing the stiffness of magnetorheological fluid contained in a fabric by applying a magnetic field has considerable potential in engineering applications. In this work, we have used a spacer (three dimensional) fabric to contain the magnetorheological fluid and then investigated the changes in the stiffness value of the composite material by applying magnetic field using neodymium-iron-boron permanent magnets. Compression tests were performed at different temperatures with and without the application of a magnetic field. It was observed that the stiffness properties of the magnetorheological fluid-filled spacer fabric were increased significantly upon the application of the magnetic field at ambient temperature; however, a decrease in the stiffness value of the magnetorheological-spacer fabric composite was observed when the tests were carried out at higher temperatures. A considerable increase in the thermal conductivity of the magnetorheological fluid-containing spacer fabric was obtained under the influence of an applied magnetic field.
Keywords: magnetorheological fluid; spacer fabric; smart structures; compression; thermal conductivity; STRUCTURE EVOLUTION; HEAT-TRANSFER; DESIGN; MODEL